Metabolic modulation of immune checkpoints and novel therapeutic strategies in cancer. (November 2022) - Wang, Yi; Wang, Yuya; Ren, Yifei; Zhang, Qi; Yi, Ping; Cheng, Chunming
Abstract: Cytotoxic T-lymphocyte–associated antigen-4 (CTLA-4) or programmed death-1 (PD-1)/programmed death-ligand 1 (PD-L1)–based immune checkpoint inhibitors (ICIs) have led to significant improvements in the overall survival of patients with certain cancers and are expected to benefit patients by achieving complete, long-lasting remissions and cure. However, some patients who receive ICIs either fail treatment or eventually develop immunotherapy resistance. The existence of such patients necessitates a deeper understanding of cancer progression, specifically nutrient regulation in the tumor microenvironment (TME), which includes both metabolic cross-talk between metabolites and tumor cells, and intracellular metabolism in immune and cancer cells. Here we review the features and behaviors of the TME and discuss the recently identified major immune checkpoints. We comprehensively and systematically summarize the metabolic modulation of tumor immunity and immune checkpoints in the TME, including glycolysis, amino acid metabolism, lipid metabolism, and other metabolic pathways, and further discuss the potential metabolism-based therapeutic strategies tested in preclinical and clinical settings. These findings will help to determine the existence of a link or crosstalk between tumor metabolism and immunotherapy, which will provide an important insight into cancer treatment and cancer research.